Decision-Making Process Of Corporate-Farming Innovation In Bantul Regency - Alia Bihrajihant Raya; Siti Fatonah; Ratih Ineke Wati; Sri Peni Wastutiningsih (Agro Ekonomi, 2021)
Corporate farming is an agricultural innovation to answer narrow land tenure problems due to widespread land conversion and land fragmentation. The principle of corporate farming is land consolidation with one joint management. This research attempts to determine the decision-making process for corporate farming innovation in Bantul Regency, using an exploratory approach with the Social Network Analysis (SNA) method and ego-centered network analysis. The ego in this study is the innovator and chairman of the corporate farming team. The results of the study were presented in a sociogram using Pajek software. The actors involved in the corporate farming innovation decision-making process are the head of farmer groups, administrators, team leaders, member farmers, Bantul Regency Agricultural Service, local extension agents, and stakeholders including the Research Team of the UGM Faculty of Agriculture, Bank Indonesia Regional DIY, and BPTP DIY. The introduction stage was carried out in a farmer group meeting, and the UGM Faculty of Agriculture Research Team acts as the innovator. It is followed by the persuasion stage, which explains the benefits of implementing corporate farming during subsequent farmer group meetings. The decision stage is indicated by providing direction, assistance, and financial support, which relied on group agreement to commit corporate farming. The farmer groups’ heads dominated the persuasion stage, the decision stage, and the implementation stage. The differences between corporate farming and individual farming lie in some aspects, such as working together rather than individual work, semi-organic cultivation systems, and optimizing the use of agricultural machinery. At the confirmation stage, 62% of informants disagree to continue corporate farming due to significant drops in production yields. The change in the cultivation system from chemical to semi-organic is one reason for the decline in production.Keywords: corporate farming, ego-centered network, decision-making process, social network analysis